Simplicity is the Ultimate Sophistication – Role of a Catheter Mount and a Laparoscopic Washer in the Removal of an Intrabronchial Foreign Body - S Divyashree; Vinod Krishnagopal; A Shanmuga Priya; Raj Murugan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Foreign body retrieval from the airway can be quite challenging due to various concerns such as sharing of the airway between the anesthesiologist and pulmonologist, reduced functional residual capacity, ventilation-perfusion mismatch, etc. Flexible fiberoptic bronchoscopy through supraglottic airway devices has been preferred over rigid bronchoscopy for foreign body retrieval as there is better control of the airway, provides access to distal airways, and allows bronchoalveolar lavage. However, intermittent pauses in positive pressure ventilation could be deleterious in patients with reduced functional residual capacity. The incorporation of a catheter mount with a laparoscopy washer in the suction port will enable the simultaneous execution of ventilation and foreign body extraction. We have successfully used the above technique in the retrieval of an intrabronchial foreign body from a 65-year-old obese man.